Recent Advancements in Ocean Current Turbine Blade Design: A Review of Geometrical Shape, Performance and Potential Development Using CAE - Aprianur Fajri; Martin Jurkovič; Enock Michael Kandimba; Agus Lutanto; Fajrul Falah; Ristiyanto Adiputra; Nurman Firdaus (Mekanika: Majalah Ilmiah Mekanika, 2024)
The global energy demand is experiencing a significant surge, reaching 442 exajoules in 2023. The urgency to develop renewable energy sources intensifies as global energy needs continue to escalate, coupled with the detrimental impact of fossil fuel consumption on climate change. Ocean current energy has emerged as a promising renewable energy source due to its predictability and minimal environmental impact. However, the efficiency and reliability of Ocean Current Turbines (OCTs) depend highly on their blades' design and performance. This review provides a comprehensive overview of recent advancements in ocean current and tidal current turbine blade design and the challenges and issues associated with their operation and maintenance. The paper discusses various design aspects, including blade geometry, material selection, hydrodynamic performance optimization, and bio-inspired designs. Additionally, it highlights the common failures and degradation mechanisms of turbine blades, such as fatigue, erosion, and cavitation. Furthermore, the review explores the challenges faced in developing and deploying OCTs, such as improved blade durability, cost-effectiveness, and environmental compatibility.